2006
DOI: 10.1016/j.clpt.2006.04.010
|View full text |Cite
|
Sign up to set email alerts
|

VKORC1 gene variations are the major contributors of variation in warfarin dose in Japanese patients

Abstract: The ethnic difference in warfarin maintenance dose was mainly dependent on the linked VKORC1 variants. Genotyping of -1639 G>A of the VKORC1 gene could be clinically important for predicting individual variability in anticoagulant responses to warfarin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
85
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(94 citation statements)
references
References 36 publications
7
85
2
Order By: Relevance
“…1,2 To meet the demands of medicine in the post-genome era, high-throughput, straightforward, and high-performance genotyping is required. Various assays have been developed to analyze SNP genotypes, including direct DNA sequencing after polymerase chain reaction (PCR) amplification, 3 PCR-restriction fragment length polymorphism (PCR-RFLP), 4 TaqMan PCR, 5 and allele-specific primer-PCR (ASP-PCR). 6 SNP genotyping can generally be divided into two steps: sample preparation, typically purification of DNA from biological specimens, such as blood and allele detection.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 To meet the demands of medicine in the post-genome era, high-throughput, straightforward, and high-performance genotyping is required. Various assays have been developed to analyze SNP genotypes, including direct DNA sequencing after polymerase chain reaction (PCR) amplification, 3 PCR-restriction fragment length polymorphism (PCR-RFLP), 4 TaqMan PCR, 5 and allele-specific primer-PCR (ASP-PCR). 6 SNP genotyping can generally be divided into two steps: sample preparation, typically purification of DNA from biological specimens, such as blood and allele detection.…”
Section: Introductionmentioning
confidence: 99%
“…A single common VKORC1 SNP Ϫ1639/3673 AϾG defines VKORC1 haplotypes with increased sensitivity to warfarin (group A haplotypes, H1 and H2). [1][2][3][4][5][6][7][8][9] CYP2C9 is responsible for metabolism of Ͼ90% of S-warfarin, the more active enantiomer of warfarin. Two common allelic variants of CYP2C9 with reduced enzymatic activity (CYP2C9*2 and CYP2C9*3) have been associated with reduced metabolism of warfarin, lower required doses of warfarin to achieve adequate anticoagulation, and increased risk of adverse events when beginning warfarin therapy.…”
mentioning
confidence: 99%
“…Previous studies in patients with different CYP2C19 genotypes reported not to affect plasma R-warfarin concentrations at the steady state in clinical studies, in which the concentrations were evaluated at a one sampling point (Obayashi K et al, 2006;Scordo MG et al, 2002;Takahashi et al, 1998). However, two of the reports (Obayashi K et al, 2006;Scordo MG et al, 2002) observed that the S/R ratio based on steady-state concentrations in PMs was smaller than that in hmEMs.…”
Section: The Effect Of Cyp2c19 Genotypes On the Pharmacokineticsmentioning
confidence: 61%
“…However, two of the reports (Obayashi K et al, 2006;Scordo MG et al, 2002) observed that the S/R ratio based on steady-state concentrations in PMs was smaller than that in hmEMs. The third study (Takahashi et al, 1998) compared PMs with EMs which included both hmEMs and heterozygous EMs with one mutated CYP2C19 allele.…”
Section: The Effect Of Cyp2c19 Genotypes On the Pharmacokineticsmentioning
confidence: 99%
See 1 more Smart Citation